2019
DOI: 10.1177/0840470419867344
|View full text |Cite
|
Sign up to set email alerts
|

Alberta’s Strategic Clinical Networks: A roadmap for the future

Abstract: Clinical networks are groups of clinicians, patients, operational leaders, and other stakeholders who work together to solve health challenges, translate evidence into practice, and improve health outcomes and clinical care. Networks enable health, community, and academic partners to align their efforts, address priority issues, and advance quality improvements, health innovation, and transformational change on a local and system-wide scale. Clinical networks have existed in some countries for nearly 20 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Alberta has 16 strategic clinical networks that were modelled on the clinical networks in England and Scotland. 20 General information on Alberta's strategic clinical networks is summarized in Table 4. Three examples of the impact of strategic clinical networks working together with operational leaders and programs within Alberta are highlighted, including improving appropriate antipsychotic use in dementia, enhancing recovery after surgery and the provincial stroke action plan.…”
Section: Alberta Canadamentioning
confidence: 99%
See 2 more Smart Citations
“…Alberta has 16 strategic clinical networks that were modelled on the clinical networks in England and Scotland. 20 General information on Alberta's strategic clinical networks is summarized in Table 4. Three examples of the impact of strategic clinical networks working together with operational leaders and programs within Alberta are highlighted, including improving appropriate antipsychotic use in dementia, enhancing recovery after surgery and the provincial stroke action plan.…”
Section: Alberta Canadamentioning
confidence: 99%
“…8 Having a set of core principles by which networks operate appears to enable network performance, 18 even in mandated clinical networks, and experience suggests that networks lacking close partnerships with operational leaders and managers are unlikely to be successful. 20 Some early learnings on barriers, and facilitators to network success within a Canadian setting, are available from recent stakeholder consultations on Alberta's strategic clinical networks. 20 Many themes emerged, including the critical importance of engagement with patient and family advisers (including co design of interventions) and health system partners.…”
Section: What Influences the Effectiveness Of Clinical Network?mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Since 2015, about 20 projects that showed a positive and substantial effect for patients and the health system have been implemented on a provincial scale. 7 Ten of these are profiled in a 2019 report that described the effect of SCNs on health outcomes, 2 and all involved evidence-informed changes in clinical practice. The SCNs have helped to improve the use of appropriate antipsychotics in patients with dementia, supported the implementation of enhanced recovery after surgery protocols and the safe surgery checklist, improved access to diagnosis for patients with breast cancer and supported the implementation of a provincial stroke action plan (Stroke Care Alberta).…”
mentioning
confidence: 99%
“…They emphasized the importance of communication and coordination across networks, and the need to expand relationships with primary health care and community partners, research institutes and other health organizations. 7 Stakeholders acknowledged the inherent tension that exists between SCNs and local operational priorities. Participants also suggested that shared planning and participation in quality, safety and operational committees would provide opportunities to align resources, clinical objectives and efforts for quality improvement.…”
mentioning
confidence: 99%